1997
DOI: 10.1007/bf03392917
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies Examining the Nature of Selection-based and Topography-based Verbal Behavior

Abstract: Selection-based (SB) verbal behavior, in most general terms, consists of selecting stimuli from an array, which presumably has some effect on a listener. Topography-based (TB) verbal behavior consists of responses with unique topographies (e.g. speaking, signing, writing) which is also presumed to have some effect on a listener. This article reviews research examining the nature of these two types of verbal behavior. Overall, TB verbal behavior appears to be more easily acquired and may also function to mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…In fact, anecdotal evidence suggests that location discrimination may have occurred during some later sessions, but posttest scores provide evidence against such a simple discrimination. Our results complement those of Potter and Brown (1997) in suggesting that selection-based responses promote the acquisition of topography-based responses, at least in the context of MTS protocols. In addition, evidence of discrimination between accurate and inaccurate stimuli was suggested by both participants' behavior, (question 2 for Mike and question 1 and question 2 for Carla).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, anecdotal evidence suggests that location discrimination may have occurred during some later sessions, but posttest scores provide evidence against such a simple discrimination. Our results complement those of Potter and Brown (1997) in suggesting that selection-based responses promote the acquisition of topography-based responses, at least in the context of MTS protocols. In addition, evidence of discrimination between accurate and inaccurate stimuli was suggested by both participants' behavior, (question 2 for Mike and question 1 and question 2 for Carla).…”
Section: Resultssupporting
confidence: 80%
“…Since Michael's seminal paper on the topic, researchers have continued to clarify the distinction between selectionbased and topography-based verbal behavior. Potter and Brown (1997) have suggested that topography-based responses might promote the acquisition of selectionbased responses in some contexts, especially in participants with extensive verbal repertoires. In examining the role of such verbal behavior, found that participants preferred selection-based tasks which incorporated a topography-based component when taught relations between sample stimuli consisting of flag-like patterns and comparison stimuli consisting of dot patterns.…”
mentioning
confidence: 99%
“…Not surprisingly, therefore, their learning of vocal verbal behavior is often poor, particularly in the case of severely mentally retarded individuals. Manual sign training, however, often has proved to be a more effective means of establishing verbal behavior in such populations (Kahn, 1981;Potter & Brown, 1997;Sundberg, 1993). In addition to an increase in social interaction as the sign repertoire develops (Lloyd, 1976), there is evidence of a concomitant reduction in challenging behaviors (e.g., Casey, 1978).…”
Section: The Applied Significance Of Manual Namingmentioning
confidence: 99%
“…Selecting a form of augmentative communication often involves a decision between a selection-based form of verbal behavior (e.g., the picture exchange communication system) (Frost & Bondy, 1994) and a topography-based form of verbal behavior (e.g., sign language). Conceptual analyses and research based on Skinner's Verbal Behavior suggest that selection-based systems involve multiple response forms (e.g., scanning, selecting, handing over) and conditional discriminations that are more complex than they first appear (e.g., Lowenkron, 1991;Michael, 1985;Potter & Brown, 1997;Potter, Huber, & Michael, 1997;Shafer, 1993;C. T. Sundberg & Sundberg, 1990;M.…”
Section: More General Issuesmentioning
confidence: 99%